Hyaluronic acid cryogels with non-cytotoxic crosslinker genipin - Johanna Roether; Claude Oelschlaeger; Norbert Willenbacher (Materials Letters: X, 2019)
For the first time, macroporous, elastic, three-dimensional hyaluronic acid cryogels were prepared with genipin as non-cytotoxic crosslinking agent. These cryogels are characterized by a lamellar porous structure with a homogeneous pore size of ~100 µm, shear elasticity of ~2 kPa and a swelling ratio of 2.5 in water. Additionally, multiple particle tracking based microrheology measurements reveal the formation of a heterogeneous network. This novel biomaterial owns great potential as non-cytotoxic alternative for application in drug delivery, as tissue engineering scaffold or wound healing substrate and can help reducing toxicity of artificial skin grafts or tissue equivalents. Keywords: Non-cytotoxic crosslinking, Genipin, Hyaluronic acid, 3D scaffold, Cryogelation